Mindfulness Meditation for School Administrators - Wachirawangso (Kornamsai), PhraAnusorn; Somprach, Kanokorn; Vadasuddo (Khemma), PhraHonda (Journal of Graduate MCU KhonKaen Campus, 2024)
This article aimed to provide information on the development of meditation for school administrators for peace, comfort and a sense of well-being, with the aim of creating concentration on mental health and personality development of school administrators, consisting of 1) Meditation that affects the mind 2) Personality gives strength 3) Emotional stability 4) To be peaceful, cool, polite, soft, fresh, bright, energetic, dignified, benevolent. Look and know oneself and others truthfully and prepare the mind to be in a state of readiness and easy to cultivate virtues, foster good habits. Know how to calm the mind, relieve the suffering that arises in the heart. Have emotional stability, immune to mental illnesses. It can also be useful in daily life, helps the mind to relax, relieves stress, relieves anxiety, stops anxiety and worry. It is a tool to relax the mind and happiness, promote efficiency at work, study and all business activities.